2002
DOI: 10.1126/science.1068793
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor and Electron Microscopic Imaging of Connexin Trafficking

Abstract: Recombinant proteins containing tetracysteine tags can be successively labeled in living cells with different colors of biarsenical fluorophores so that older and younger protein molecules can be sharply distinguished by both fluorescence and electron microscopy. Here we used this approach to show that newly synthesized connexin43 was transported predominantly in 100- to 150-nanometer vesicles to the plasma membrane and incorporated at the periphery of existing gap junctions, whereas older connexins were remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
682
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 873 publications
(717 citation statements)
references
References 26 publications
29
682
1
5
Order By: Relevance
“…More recent studies using epitope and fluorescent protein-tagged Cx43 support the mechanism of GJ internalization by annular junctions Gaietta et al, 2002]. Mechanistic analyses revealed that components of the clathrin-dependent endocytosis machinery are directly involved in the internalization, inward movement, and initial degradation of these intercellular double-membrane vesicles.…”
Section: Gap Junction Removal and Degradationmentioning
confidence: 94%
See 1 more Smart Citation
“…More recent studies using epitope and fluorescent protein-tagged Cx43 support the mechanism of GJ internalization by annular junctions Gaietta et al, 2002]. Mechanistic analyses revealed that components of the clathrin-dependent endocytosis machinery are directly involved in the internalization, inward movement, and initial degradation of these intercellular double-membrane vesicles.…”
Section: Gap Junction Removal and Degradationmentioning
confidence: 94%
“…Connexon-containing cargo-vesicles may fuse with the plasma membrane in the center of plaques or at their marginal boundaries, followed by lateral diffusion in the plasma membrane to reach the plaque site. According to Gaietta et al [2002], the latter pathway seems to be the preferred route for plaque renewal with removal of older connexons from the center of the plaques. Incorporation of new connexons preferentially at the periphery of plaques indicated that a directed transport of connexons via cargo-vesicles is fundamental for GJ assembly (see also below).…”
Section: Shuttling To the Plasma Membrane And Intramembrane Movementmentioning
confidence: 99%
“…While hemichannels are inevitably present in gap junction expressing cells because gap junctions are formed after docking to newly assembled hemichannels in adjacent cells [66], their opening, which becomes prominent under pathological conditions, could result in release of a series of biologically relevant signaling molecules such as ATP, glutamate, glutathione, NAD + , and prostaglandin E2 [65]. Hemichannels made by Cx43 or structurally related connexins, if presented in mature ORNs, will be impaired in OlfDNCX.…”
Section: Discussionmentioning
confidence: 99%
“…A small peptide with a bright associated dye would be an ideal tag and may be possible. The FlAsH/ReAsH peptide tagging system [110, 111] is currently the smallest commercially available tag. One of the major shortcomings is the lack of suitability for the secretory pathway.…”
Section: Perspectivementioning
confidence: 99%